(untitled) (Mediscope, 2024)
Human Immunodeficiency Virus Type 1 (HIV-1) is a condition that affects over 60 million people worldwide. Viral infection can be controlled using highly active antiretroviral therapy (HAART) to suppress HIV-1 replication and hinder disease progression, but viremia quickly rebounds following HAART interruption. It is highly likely that the persistence of virus occurs predominantly in latently infected CD4+ T cells, a new strategy to eradicate HIV-1. Previously it has been shown that the viral reservoir is seeded rapidly following the initial infection of rhesus macaques with SIV, even before the establishment of a systemic infection, so destroying this reservoir may be vital to the effective clearance of HIV. We reasoned that long-lived tissue macrophages contribute significantly to the SIV/HIV reservoir, such as those that may be found in adipose tissue. Mediscope 2024;11(2): 68-72